Synthesis and vibrational spectra of bimetallic compounds of the type [(NH3)(L)ZnFe(CO)4] (L = bidentate amine - Mauro, A. E. [UNESP]; Mancini, M. N. G. [UNESP] (Elsevier B.V., 1984)
New compounds with the general formulae [(NH3)(L)ZnFE(CO4] (L = ethylenediamine, N-methylethylenediamine, N,N′-dimethylethylenediamine and 1,3-propanediamine) were prepared and studied by vibrational spectroscopy. The data suggest that they may be formulated as monomers with a trigonal bipyramidal configuration around the iron atom. © 1984.